Carbon Nanotubes for Targeted Drug Delivery - Hasnain, Md Saquib; Nayak, Amit Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book provides a detailed introduction to carbon nanotubes (CNTs) for targeted drug delivery. After a brief overview of the classification, preparation, and characterization of carbon nanotubes, it focuses on their use in targeted drug delivery. It presents CNTs for brain targeting, ocular targeting, cancer targeting, and lymphatic targeting, as well as antibody therapy. The book also includes chapters on carbon nanotubes for controlled drug delivery, transdermal drug delivery, solubility enhancement, vaccine delivery, gene delivery, and as quantum dots. Last but not least, it addresses the absorption and transportation of CNTs, toxicity and regulatory considerations, as well as clinical trials and the market status of CNTs. .
Introduction -- Chemical and physical properties of Carbon Nanotubes -- Classification of Carbon Nanotubes -- Preparation of Carbon Nanotubes -- Functionalization of Carbon Nanotubes -- Carbon Nanotubes Characterization -- Applications of Carbon Nanotubes -- Carbon Nanotubes absorption and transportation -- Carbon Nanotubes Toxicity Consideration -- Carbon Nanotubes Regulatory considerations -- Carbon Nanotubes Clinical trials and market status -- Conclusion.
Keywords: Nanotechnology; Pharmaceutical chemistry; Microtechnology; Microelectromechanical systems; Pharmacovigilance; Nanotechnology; Pharmaceutics; Microsystems and MEMS; Drug Safety and Pharmacovigilance